Preoperative complications in children with mesenteric lymphatic malformations: Incidence, risk factors and outcomes - Yan, Jiayu; Wang, Li; Xie, Chuanping; Peng, Chunhui; Pang, Wenbo; Chen, Yajun (Frontiers in Pediatrics, 2022)
Background: Preoperative complications of mesenteric lymphatic malformations (ML) in children are various and complex. We aim to analyze the incidences and risk factors of three major preoperative complications (hemorrhage of the cyst, infection of the cyst and intestinal volvulus) in ML patients, and explore their influence on the outcomes. Methods: This retrospective cohort study enrolled ML patients undergoing surgery at Beijing Children’s Hospital between June 2016 and June 2022 and classified them according to different preoperative complications, preoperative hemorrhage or infection, and preoperative intestinal volvulus. The groups were examined and compared according to sex, age at admission, presenting symptoms, laboratory examinations, imaging examinations, preoperative treatments, cyst characteristics, surgical details, perioperative clinical data, and follow-up. Logistic regression analysis was performed to identify the independent risk factors for preoperative hemorrhage or infection, and preoperative intestinal volvulus. Results: Of the 104 enrolled ML patients, 27 (26.0%) had preoperative hemorrhage or infection, and 22 (21.2%) had preoperative intestinal volvulus. Univariate analysis showed that patients with preoperative hemorrhage or infection had a higher rate of ML in the mesocolon (44.4 vs. 23.4%, p < 0.038) and larger cysts (10 vs. 8 cm, p = 0.042) than patients without preoperative hemorrhage or infection. Multivariable logistic regression analysis found that the location (OR, 3.1; 95% CI, 1.1-8.6; p = 0.026) and size of the cyst (≥ 7.5 cm) (OR, 6.2; 95% CI, 1.6-23.4; p = 0.007) were independent risk factors for preoperative hemorrhage or infection. Preoperative intestinal volvulus was only found in ML at the intestinal mesentery. Further analysis showed that ML in the jejunal mesentery was an independent risk factor for preoperative intestinal volvulus (OR, 3.3; 95% CI, 1.1-10.0; p = 0.027). Patients with preoperative hemorrhage or infection spent more on hospitalization costs than patients without preoperative hemorrhage or infection (3000 vs. 2674 dollars, p = 0.038). Conclusions: ML patients should be treated as soon as possible after diagnosis. The location and size of the cyst were independent risk factors for preoperative hemorrhage or infection. ML in the jejunal mesentery was an independent risk factor for preoperative intestinal volvulus.